2016
DOI: 10.1098/rspb.2015.1708
|View full text |Cite
|
Sign up to set email alerts
|

Joint torques in a freely walking insect reveal distinct functions of leg joints in propulsion and posture control

Abstract: Determining the mechanical output of limb joints is critical for understanding the control of complex motor behaviours such as walking. In the case of insect walking, the neural infrastructure for single-joint control is well described. However, a detailed description of the motor output in form of time-varying joint torques is lacking. Here, we determine joint torques in the stick insect to identify leg joint function in the control of body height and propulsion. Torques were determined by measuring whole-bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 39 publications
8
80
0
Order By: Relevance
“…Instead, the articulation of the trochanter and femur interlocks the segments, particularly on its dorsal aspect (Schindler, 1979). These features should provide high stability, which may be essential as the body coxa joints in stick insects are highly mobile (Cruse and Bartling, 1995; Dallmann et al, 2016). This mobility permits the forces generated by legs to be directed in a number of orientations relative to the body.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Instead, the articulation of the trochanter and femur interlocks the segments, particularly on its dorsal aspect (Schindler, 1979). These features should provide high stability, which may be essential as the body coxa joints in stick insects are highly mobile (Cruse and Bartling, 1995; Dallmann et al, 2016). This mobility permits the forces generated by legs to be directed in a number of orientations relative to the body.…”
Section: Discussionmentioning
confidence: 99%
“…This mobility permits the forces generated by legs to be directed in a number of orientations relative to the body. Recent studies, that have measured the ground reaction forces in freely moving stick insects, have shown that, unexpectedly, the largest torques generated in walking occur at the CTr joint (Dallmann et al, 2016). Extensive rotational forces also occur (pronation/supination) that could be damaging if the TrF joint were mobile.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations